Seroprevalence of hantaviruses and Leptospira in muskrat and coypu trappers in the Netherlands, 2016. Issue 1 (1st January 2018) - Friesema, Ingrid H. M.; Bakker, Jacinta; Maas, Miriam; Goris, Marga G. A.; van der Giessen, Joke W. B.; Rockx, Barry H. G.
ABSTRACT: Aims: Seoul orthohantavirus (SEOV) and Leptospira spp. are zoonotic pathogens with rats as main reservoir. Recently, the presence of SEOV in brown rats was reported in one region in the Netherlands. Brown rats are a frequent bycatch in traps placed to catch muskrats ( Ondatra zibethicus ) and coypus ( Myocastor coypus ), and thus are a potential health risk for trappers. It was our aim to determine the seroprevalence of orthohantavirus, specifically SEOV, and Leptospira spp in Dutch trappers.Methods and results: Participating trappers provided serum samples and completed an online questionnaire. The serum was tested for the presence of antibodies against six orthohantaviruses and eight Leptospira serovars. Two hundred-sixty trappers completed the online questionnaire (65%), and 246 (61%) and 162 (40%) serum samples were tested for relevant orthohantaviruses and Leptospira spp., respectively. The seroprevalence of Puumala orthohantavirus in Dutch trappers was 0.4% (95% CI: 0.1–2.3%). None of the participants tested positive for SEOV. The seroprevalence of leptospirosis was 1.2% (95% CI: 0.3–4.4%), although Leptospira spp. are present in brown rats in the Netherlands.Significance of study: The results indicate that the infections with orthohantaviruses and leptospires is low for muskrat and coypu trappers.